Important the marking of dental prosthesis in the recognition of people: description of two techniques - Sanchez Sandoval, Gabriela Aracely (2020)
The recognition of people who lose their lives in natural disasters or accidents are complicated when the victims are total edentulous, therefore, the need to look for new forms of identification that are reliable and easy to be implemented. Taking into account this premise, a search of the information in the literature was carried out in order to demonstrate that the marking of dental prostheses is important in the recognition of people and that they can be implemented by the government of Peru. For which three marking techniques were chosen: QR code, Digital cards and Incorporation of metal band. A rigorous selection procedure of the information was carried out in the databases, Pubmed, Scielo and VHL (Virtual Health Library), with articles published between 2012-2019, in Spanish and English. 105 articles were found of which only 18 of them were chosen, which met the inclusion criteria. It is concluded that this technique is important in the identification of people, and it is suggested to consider its implementation in our country. At the end, two prosthesis marking techniques are presented on models taken from a simulator.